Synergistic Effects of Heat-Treated Green Tea Extract and Enzymatically-Modified Isoquercitrin in Preventing Obesity - Moon, Ye-jin; Kim, Hee-seong; Kim, Min-ji; Im, Hyeon-yeong; Lee, Yun-hee (Nutrients, 2023)
Previous research has shown that both heat-treated green tea extract (HTGT) and enzymatically modified isoquercitrin (EMIQ) have anti-obesity effects. Given the absence of in vivo evidence demonstrating their synergistic effects, our study aimed to elucidate the combined obesity prevention potential of HTGT and EMIQ in mice. Mice were treated with these compounds for 8 weeks, while being fed a high-fat diet, to investigate their preventive anti-obesity effects. We demonstrated that the co-treatment of HTGT and EMIQ results in a synergistic anti-obesity effect, as determined by a Kruskal–Wallis test. Furthermore, the combined treatment of HTGT and EMIQ was more effective than orlistat in reducing body weight gain and adipocyte hypertrophy induced by high-fat diet. The co-treatment also significantly reduced total body fat mass and abdominal fat volume. Additionally, the group receiving the co-treatment exhibited increased energy expenditure and higher glucose intolerance. We observed a dose-dependent upregulation of genes associated with mitochondrial oxidative metabolism and PKA signaling, which is linked to lipolysis, in response to the co-treatment. The co-treatment group displayed elevated cAMP levels and AMPK activation in adipose tissue and increased excretion of fecal lipids. The results indicate that the co-treatment of HTGT and EMIQ holds the potential to be a promising combination therapy for combating obesity. To further validate the anti-obesity effect of the combined treatment of HTGT and EMIQ in human subjects, additional clinical studies are warranted.